Konsep Bangsa dan Negara: Ketertiban Dunia dan Perdamaian Abadi - Subahan Subahan; Cinta Nor Azizah; Selvani Selvani; Fatimah Kamilah Qutrun Nada; Surya Sukti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This research discusses in detail the concepts of nation and state and their relationship in creating global peace and lasting peace amidst the ever-evolving complexity of world life. A nation is understood as a group of people who share a common identity such as history, culture, language, and shared ideals, while a state is an organization authorized to regulate the lives of citizens within a territory through a sovereign government system. This research applies a qualitative method with a literature study approach derived from books, academic journals, and official documents, using descriptive-analytical and interpretive analysis to understand the relationship between these concepts. The results of the study reveal that the nation and state are complementary, where the nation serves as a socio-cultural foundation, while the state plays a political instrument to achieve collective goals. The evolution of the state from traditional to modern forms, especially in the context of the nation-state, reflects a transition towards a more democratic system based on the principle of popular sovereignty. On a global scale, international order serves as the primary basis for achieving peace, which not only means the absence of conflict, but also includes social justice, respect for human rights, and the equitable distribution of prosperity. However, various issues such as armed conflict, economic inequality, terrorism, and climate change demonstrate that achieving peace requires strong global cooperation and a shared commitment from every nation. Therefore, a deep understanding of the concepts of nation and state is crucial as a foundation for creating a more stable, just, and peaceful world order.